Uniparental disomy for chromosome 1 with POMGNT1 splice-site variant causes muscle-eye-brain disease - Liu, Yi-Dan; Tan, Dan-Dan; Song, Dan-Yu; Fan, Yan-Bin; Fu, Xiao-Na; Ge, Lin; Wei, Wei; Xiong, Hui (Frontiers in Genetics, 2023)
POMGNT1, encoding protein O-mannose beta-1,2-N-acetylglucosaminyltransferase 1, is one of the genes responsible for dystroglycanopathy (DGP), which includes multiple phenotypes such as muscle-eye-brain disease (MEB), congenital muscular dystrophy (CMD) with intellectual disability, and limb-girdle muscular dystrophy (LGMD). Here, we report a case of MEB that is the result of a homozygous variant of POMGNT1 that is revealed through uniparental disomy (UPD). An 8-month-old boy was admitted with mental and motor retardation, hypotonia, esotropia, early onset severe myopia, and structural brain abnormalities. A panel testing of genetic myopathy-related genes was used to identify a homozygous c.636C>T (p.Phe212Phe) variant in exon 7 of POMGNT1 in the patient, a heterozygous c.636C>T variant in the father, and the wild type in the mother. Quantitative polymerase chain reaction (q-PCR) revealed no abnormal copy numbers in exon 7. Trio-based whole-exome sequencing (trio-WES) revealed a possible paternal UPD on chromosome 1 of the patient. Chromosomal microarray analysis (CMA) revealed a 120,451 kb loss of heterozygosity (LOH) on 1p36.33-p11.2, encompassing POMGNT1, and a 99,319 kb LOH on 1q21.2-q44, which indicated UPD. Moreover, RNA sequencing (RNA-seq) verified that the c.636C>T variant was a splice-site variant, leading to skipping of exon 7 (p.Asp179Valfs*23). In conclusion, to the best of our knowledge, we present the first case of MEB caused by UPD, providing valuable insights into the genetic mechanisms underlying this condition.